United Kingdom : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report, 2022)
The UK's rapid vaccination campaign enabled it to start to reopen the economy in the Spring of 2021. With highly accommodative policies, the recovery has been faster than expected. However, capacity constraints and rising price pressures have emerged while new Covid-19 variants have raised new uncertainties. The government has allowed all initial pandemic support programs to sunset but has loosened near-term fiscal policy while specifying a back-loaded medium-term consolidation plan. With continued above-target inflation readings, the BoE made a first move to raise the policy rate in December. Macroprudential policies are returning to more standard risk settings. The near-term growth outlook remains strong, but so too are price pressures, while the financial cycle remains ahead of the economic cycle. The pandemic and Brexit have magnified structural challenges. Real GDP would remain below its pre-pandemic trend by about 2-2 1/4 percent in the medium term. Risks are considerable in the period ahead, centering on new Covid-19 waves and spillovers from tensions in Eastern Europe.